RV DYSFUNCTION AND PULMANARY HYPERTENSION AS A LONG-TERM SEQUELAE OF COVID 19 ILLNESS: A STUDY AMONG PATIENTS OF SOUTH EAST ASIAN REGION - Himanshu Mahla; Lalit Kumar; Dr. Navdeep Singh Sidhu; Neeraj Chaturvedi; Manisha Keshav; Shashi Mohan Sharma; Rajeev Bagarhatta; V.V. Agrawal; Dr Shiwani Dadarwal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objectives- To study the Echocardiographic manifestations of covid 19 illness among patients admitted in our facility, Correlate MAPSE, TAPSE, PASP, CRP levels, and CTSI among covid 19 patients with their 28-day outcome as survivors and non-survivors and to look for evidence of residual RV dysfunction and Pulmonary hypertension using TTE after 1 year of follow-up.Study design- Prospective observational study at various medical wards and ICUs in SMS Medical College and associated hospitals.Methods- 258 patients with a COVID-19 RT-PCR positive report from a throat or a nasal swab within 72 hours of admission were included in the study. Each patient underwent a complete clinical assessment and routine blood investigations including CRP levels were done. A complete transthoracic echocardiogram was done within 48 hours of admission. Patients also underwent a HRCT chest and CTSI scores were estimated. All patients were followed for a period of 28 days. The MAPSE, TAPSE, PASP, CTSI and CRP levels were then correlated with the outcome of the patient. The survivors again underwent a TTE at 1 year after their recovery from covid-19 illness to look for residual RV dysfunction by TAPSE and the development of pulmonary hypertension as measured by PASP using Bernoulli’s equation.Results-Amongst patient of covid 19 illness the MAPSE, TAPSE, PASP, CTSI and CRP levels all correlated well with outcome of patients. While most covid-19 survivors recovered from their illness yet some patients showed evidence of persistent RV dysfunction and pulmonary hypertension even after 1 year of follow up